Efficacy of Curculigo orchioides in Deltamethrin Induced Reproductive System Impairment in Male Wistar Rats - Singh, Dr. Rambir (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To evaluate the ameliorating effect of Curculigo orchioides (CO) against deltamethrin (DLM) induced reproductive toxicity in male rats. Materials and Methods: A total of 42 adult male Wistar rats were divided into seven groups of six rats each. Group A (control) received normal diet and water ad-libitum, Group B (exposure) received DLM (2 mg/kg bw), orally in dimethylsulphoxide for 60 days, Group C (Treatment 1) received CO (100 mg/kg bw), orally dissolved in distilled water, Group D (Treatment 2) received CO at the dose of 200 mg/kg bw dissolved in distilled water, Group E (Combination 1) received DLM at the dose of 2 mg/kg with CO (100 mg/kg bw), Group F (Combination 2) received DLM at the dose of 2 mg/kg with CO (200 mg/kg bw), and Group G (metabolized) received DLM at the dose of 2 mg/kg bw for 60 days and DLM was left to metabolized for 60 days. Results and Discussion: DLM exposure caused significant reduction in body weight, reproductive organ weight, sperm head counts, sperm motility, reduced glutathione (GSH), catalase, superoxide dismutase (SOD), GSH-S-transferase (GST), GSH peroxidase (GPx), GSH reductase (GR), testosterone (T), follicles stimulating hormone (FSH), luteinizing hormone (LH) and steroidogenic enzyme 3Î² hydroxysteroid dehydrogenase (3Î² HSD), and 17Î² HSD. DLM exposure also showed increase in sperm abnormalities and level of lipid peroxidation. The treatment with CO improved the body weight, reproductive organ weight, sperm head count, sperm motility, and sperm abnormality. CO treatment also increased the level of GSH, SOD, GST, GPx, GR, T, FSH, LH and steroidogenic enzyme 3Î² HSD, and 17Î² HSD. Histological findings indicated vacuolation in lumen, disorganization of leydig cells and sertoli cells and inhibition of spermatogenesis in testicular tissue on DLM exposure, whereas CO treatment recovered normal histoarchitecture. Conclusion: The findings indicated that DLM damaged the reproductive system of male Wistar rats. CO treatment efficiently improved the reproductive system chiefly by increasing the level of important steroidogenic enzymes and hormones.